TEACHING PROFESSIONALLY ORIENTED READING IN FOREIGN LANGUAGES: A PSYCHOLOGICAL AND PEDAGOGICAL APPROACH (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
In the context of globalization and the rapid development of science and technology, the role of foreign languages in higher education has significantly increased. For students of non-linguistic universities, foreign language proficiency is no longer limited to everyday communication but has become an essential tool of professional interaction. Reading professionally oriented literature in a foreign language serves as a primary source of up-to-date scientific, technical, and economic information and contributes directly to the development of professional competence. This article examines the psychological and pedagogical foundations of teaching professionally oriented reading at non-linguistic universities. The study analyzes reading strategies, criteria for selecting professional texts, vocabulary and terminology acquisition, and motivational aspects of learning. Particular attention is paid to the integration of practical classroom activities in German, demonstrating how theoretical principles can be effectively implemented in teaching practice. The findings confirm that a systematic, professionally oriented approach to teaching reading significantly enhances students’ motivation, cognitive activity, and readiness for professional tasks.